Assessing the Effectiveness of the Tahfidz Program: A CIPP (Context, Input, Process, and Product) Model Evaluation Approach - Anisa, Salma; Moh. Muslih (Tadibia Islamika: Journal of Holistic Islamic Education, 2023)
This study aims to assess the implementation of the tahfidz program at Al Fawwaaz PPTQ Islamic Boarding School using the CIPP evaluation model. Employing a qualitative field research approach, the study involved the principal, deputy head of tahfidz, and tahfidz teacher as participants. Data collection techniques included observation, interviews, and documentation. Data analysis was conducted using the interactive model analysis technique proposed by Miles, Huberman, & Saldana (2014). The findings revealed that the tahfidz program aligns with student needs, community expectations, and institutional goals. Program planning is clear and purposeful. However, certain aspects require improvement, such as enhancing teacher proficiency in the classical tahsin system. The full tahfidz scholarship program initially targeted students with above-average memorization skills to complete 30 Juz Salama in three years. However, attracting students meeting these criteria proved challenging. Facilities and infrastructure are well-prepared, but specific facilities to accommodate students with auditory learning preferences are lacking. Process evaluation indicated that many students fall short of the set targets each semester, and nighttime memorization sessions are less effective. Additionally, some students prioritize fluency over proper makhraj and tajweed pronunciation. Product evaluation demonstrated positive outcomes, with memorization achievements aligning with individual student abilities. Overall, the tahfidz program at Al Fawwaaz PPTQ shows promise but requires ongoing evaluation and improvement to optimize its effectiveness.